The ultimate response guideline simulation and analysis using TRACE, MAAP5, and FRAPTRAN for the Chinshan Nuclear Power Plant. (May 2017) - Wang, Te-Chuan; Wang, Jong-Rong; Lin, Hao-Tzu; Chen, Hsiung-Chih; Chen, Shao-Wen; Shih, Chunkuan; Chiang, Show-Chyuan; Yu, Tzu-Yao
Highlights: The establishment of TRACE and MAAP5 model of Chinshan (BWR/4) NPP. The URG was simulated by TRACE and MAAP5 model to verify the concept of this emergency plan. The analysis results show that URG can keep the PCT below the failure criteria 1088.7 K under Fukushima-like conditions. The trends of TRACE prediction are consistent with MAAP5 results but there are a few differences in the predictions. Abstract: In this research, the TRACE and MAAP5 model of Chinshan BWR/4 nuclear power plant (NPP) has been established for the simulation and analysis of ultimate response guideline (URG). The main actions of URG are the depressurization and low pressure water injection of the reactor and containment venting. This research focuses to assess the usefulness of the URG under Fukushima-like conditions. This study consists of three steps. The first step is the establishment of Chinshan NPP TRACE and MAAP5 model. The second step is the URG simulation and analysis under Fukushima-like conditions by using Chinshan NPP TRACE and MAAP5 model. In this step, the base case without URG case was also performed in order to evaluate the URG effectiveness of Chinshan NPP. In order to confirm the mechanical property and integrity of fuel rods, the final step is FRAPTRAN analysis. According to TRACE and MAAP5 analysis results under Fukushima-like conditions, the URG can keep the peak cladding temperature (PCT) below the criteria 1088.7 K. It indicates that Chinshan NPP can be controlled in a safe situation. If under Fukushima-like conditions Chinshan NPP does not perform the URG, the water level may drop below the TAF (top of active fuel) which means a fuel melt safety issue may exist.